Answer:
![\left(-t^4-5t^3-10t^2\right)+\left(9t^3+3t^2-1\right)=-t^4+4t^3-7t^2-1](https://tex.z-dn.net/?f=%5Cleft%28-t%5E4-5t%5E3-10t%5E2%5Cright%29%2B%5Cleft%289t%5E3%2B3t%5E2-1%5Cright%29%3D-t%5E4%2B4t%5E3-7t%5E2-1)
Step-by-step explanation:
Given the expression
![\left(-t^4\:-5t^3\:-10t^2\:\right)+\left(9t^3\:+3t^2\:-1\right)](https://tex.z-dn.net/?f=%5Cleft%28-t%5E4%5C%3A-5t%5E3%5C%3A-10t%5E2%5C%3A%5Cright%29%2B%5Cleft%289t%5E3%5C%3A%2B3t%5E2%5C%3A-1%5Cright%29)
Remove parentheses: (a)=a
![=-t^4-5t^3-10t^2+9t^3+3t^2-1](https://tex.z-dn.net/?f=%3D-t%5E4-5t%5E3-10t%5E2%2B9t%5E3%2B3t%5E2-1)
Group like terms
![=-t^4-5t^3+9t^3-10t^2+3t^2-1](https://tex.z-dn.net/?f=%3D-t%5E4-5t%5E3%2B9t%5E3-10t%5E2%2B3t%5E2-1)
Add similar elements
∵ ![-10t^2+3t^2=-7t^2](https://tex.z-dn.net/?f=-10t%5E2%2B3t%5E2%3D-7t%5E2)
Add similar elements
∵ ![-5t^3+9t^3=4t^3](https://tex.z-dn.net/?f=-5t%5E3%2B9t%5E3%3D4t%5E3)
Thus, the equivalent expression in simplified form:
![\left(-t^4-5t^3-10t^2\right)+\left(9t^3+3t^2-1\right)=-t^4+4t^3-7t^2-1](https://tex.z-dn.net/?f=%5Cleft%28-t%5E4-5t%5E3-10t%5E2%5Cright%29%2B%5Cleft%289t%5E3%2B3t%5E2-1%5Cright%29%3D-t%5E4%2B4t%5E3-7t%5E2-1)
Answer:
1/4
Step-by-step explanation:
The inverse function tells you the input value that corresponds to the given output value of the function.
<h3>Application</h3>
You want f^-1(3), which is the value of x such that f(x) = 3.
f(x) = 3 = 4x +2
1 = 4x . . . . . . subtract 2
1/4 = x . . . . . divide by 4
The inverse function of 3 is 1/4:
![\boxed{f^{-1}(3)=\dfrac{1}{4}}](https://tex.z-dn.net/?f=%5Cboxed%7Bf%5E%7B-1%7D%283%29%3D%5Cdfrac%7B1%7D%7B4%7D%7D)
Answer:
The other dimension of the sandbox must be (4x+3).
Hope this helps! Have a good day!
Answer:
135 degrees and 45 degrees
Step-by-step explanation:
Two angles are supplementary when their sum adds up to 180 degrees.